2018
DOI: 10.22219/jinop.v4i1.4906
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Penggunaan Media Pembelajarantematik Di Sd Muhammadiyah 9 Kota Malang

Abstract: Media pembelajaran tematik merupakan media pembelajaran yang bisa menjembatani 2 atau lebih mata pelajaran yang dipelajari dalam pembelajaran tematik. Dalam pembuatan media harus sesuai dengan analisis kebutuhan dan karaktersitik pembelajaran (tujuan pembelajaran), perkembangan belajar siswa SD serta dengan mempertimbangkan alat pengukur keberhasilan belajar siswa. SD Muhammadiyah memiliki siswa yang latar belakangnya menengah ke bawah serta didukung dengan para guru SD Muhammadiyah yang hampir 50% memiliki la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
2
0
4
Order By: Relevance
“…Based on field data, it is found that thematic learning applied in schools helps and makes it easier for teachers to apply character values that have a specific relationship between the subject matter and the students' natural experiences. In line with Ekowati et al (2018) state that the main characteristic of thematic learning in primary school combines lessons with a contextual framework and deepening character values. As Hasrawati (2016) expressed, thematic learning also provides direct experience for students to absorb lessons related to life and learning to be interesting to follow.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Based on field data, it is found that thematic learning applied in schools helps and makes it easier for teachers to apply character values that have a specific relationship between the subject matter and the students' natural experiences. In line with Ekowati et al (2018) state that the main characteristic of thematic learning in primary school combines lessons with a contextual framework and deepening character values. As Hasrawati (2016) expressed, thematic learning also provides direct experience for students to absorb lessons related to life and learning to be interesting to follow.…”
Section: Discussionmentioning
confidence: 86%
“…Students use skills and knowledge from various subjects simultaneously to answer questions or solve problems. Thus, the thematic learning model is a learning model designed based on specific themes to provide students with meaningful experiences (Ekowati, Utami, & Kusumaningtyas, 2018;Narti et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Guru pada dasarnya telah mengupayakan untuk menciptakan pembelajaran tematik terpadu sebaik mungkin, namun hal ini menjadi sangat terbatas karena penggunaan media pembelajaran yang belum tepat sasaran untuk pembelajaran tematik terpadu. Guru masih menggunakan media pembelajaran yang sedanya dan kerap kali menggunakan beberapa media pembelajaran, sehingga media yang digunakan belum dapat dikatakan sebagai media pembelajaran tematik terpadu (Worowirastri E. et al, 2018). Lebih lanjut dijelaskan bahwa penggunaan media pembelajaran terpadu masih begitu minim dan belum mampu untuk menjelaskan keterpaduan konsep pembelajaran yang utuh sehingga tidak terlihat pemisahan pada materi masing-masig mata pelajaran (Meilinda et al, 2017).…”
Section: Pendahuluanunclassified
“…Guru pada dasarnya telah mengupayakan untuk menciptakan pembelajaran tematik terpadu sebaik mungkin, namun hal ini menjadi sangat terbatas karena penggunaan media pembelajaran yang belum tepat sasaran untuk pembelajaran tematik terpadu. Guru masih menggunakan media pembelajaran yang sedanya dan kerap kali menggunakan beberapa media pembelajaran, sehingga media yang digunakan belum dapat dikatakan sebagai media pembelajaran tematik terpadu (Worowirastri E. et al, 2018). Lebih lanjut dijelaskan bahwa penggunaan media pembelajaran terpadu masih begitu minim dan belum mampu untuk menjelaskan keterpaduan konsep pembelajaran yang utuh sehingga tidak terlihat pemisahan pada materi masingmasig mata pelajaran (Meilinda et al, 2017).…”
Section: Pendahuluanunclassified